Análisis para el desarrollo de un diseño electromecánico para un patio de seccionamiento en 69KV. - Chalén Rojas, Christian Gabriel (2019)
In the present work there is realized a description of the configurations used for the construction of electrical substations in 69kV according to Regulation Not. ARCONEL 001/15 in the one that indicates that " The distributor will attend to the clients' request in high voltage that they need to connect to a line of existing subtransmission, across a derivation, with the respective seccionamiento of derivation to attend to a new or existing consumer. The electromechanical design of the substation beside expiring with the procedure and Ecuadoran in force regulations must guarantee safety, reliability and selectivity of the equipments that shape it. Besides definitions there is realized a description of the auxiliary elements and the importance that they have for the control, protection and measurement of the substations of energy, also there are described the active elements and calculations that must be realized for the design of a substation.